1978
DOI: 10.1136/bmj.2.6130.96
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of hypertensive emergencies with oral labetalol.

Abstract: the right leg at age 52 and later of left leg. No history of DVT; no family history of leg ulcers. Left inguinal herniorrhaphy at age 45. Case 2-Born 1915, single, height 1-8 m, weight 95 3 kg. Ulceration of left leg at age 39. Mild eczema of the right leg. No history of DVT. Mother and maternal aunt had leg ulcers. Case 3-Born 1944, single, height 1 8 m, weight 93-9 kg. Ulceration of the right leg at age 29. Four years previously he injured the right foot. This was followed by DVT and pulmonary embolus. Case … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1979
1979
1998
1998

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…More recently a 'single oral dose of 300-400 mg labetalol has been found to be effective in rapidly controlling severe hypertension. Similar results have been reported by Ghose et al (1978).…”
Section: Discussionsupporting
confidence: 82%
“…More recently a 'single oral dose of 300-400 mg labetalol has been found to be effective in rapidly controlling severe hypertension. Similar results have been reported by Ghose et al (1978).…”
Section: Discussionsupporting
confidence: 82%
“…It is interesting to note that the speed of onset following oral administration is also rapid. A significant hypotensive response is seen between 1.5-2 h, and Ghose et al (1978) have suggested that the oral preparation is quite acceptable for the treatment of most hypertensive emergencies. This rapid reduction in BP seen following oral administration is almost certainly due to the a-adrenoceptor-blocking component, as we have shown along with other workers that both the selective and non-selective B-adrenoceptor-blocking drugs will only produce a significant reduction in systolic and diastolic BPs after the lapse of at least 12-24 hours.…”
Section: Discussionmentioning
confidence: 96%
“…After the administration of the radiolabelled drug, high levels of radioactivity have been found in liver, lung and kidney (Martin et al, 1976 (Louis et al, 1978a;Louis et al, 1978b) and in most clinical situations the drug is best given in divided doses. Unlike other ,B-adrenoceptor-blocking drugs, labetalol causes a significant fall in BP following single doses of the drug given either intravenously of orally (Koch 1976;Ghose et al, 1978). After the intravenous dose there was a significant effect on both systolic and diastolic BPs within 5 minutes.…”
Section: Physiological Measurementsmentioning
confidence: 93%